PENGARUH MODEL PEMBELAJARAN RECIPROCAL TEACHING TERHADAP HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN PPKn DI SMK NEGERI 1 KOTA TANGERANG SELATAN - Rachmawaty, Shella; Mulyana, Ahmad Nana Mahmur (Eduka : Jurnal Pendidikan, Hukum, dan Bisnis, 2024)
Using a quantitative experimental design approach, this study aims to evaluate the impact of using reciprocal teaching on learners' learning outcomes. The reciprocal teaching model, which emphasises collaboration between teachers and learners, involves four main strategies: summarising, questioning, clarifying and predicting. After the treatment, the average score of students' learning outcomes in the experimental class increased to 82.43, while in the control class it increased to 64.17, with a difference (Mean Difference = 18.266). Before treatment, the average value of students' learning outcomes in the experimental class was 61.62, while in the control class it was 59.31. The Independent Sample T-Test test results indicated a significant difference (Sig = 0.000 <0.05) between the experimental and control groups. This confirms that students who followed the reciprocal teaching learning model experienced a higher increase in learning outcomes than the control group who used the direct instruction learning model. This finding indicates that the use of the reciprocal teaching learning model has an effect on the learning outcomes of students in PPPKn subjects at SMK Negeri 1 South Tangerang City.